CFO’s Working as The Board Secretary Concurrently and Corporate Disclosure Quality: Based on Empirical Evidence of Listed Companies in Shenzhen Stock Exchange - Rui, Xiang; Xing, Qian (International Journal of Accounting & Finance Review, 2020)
This paper took the selected data listed companies in Shenzhen Stock Exchange in 2008-2015 as samples to study the relationship between the CFO’s working as the Board Secretary concurrently and corporate disclosure quality, and also to examine the impact of different government intervention levels and nature of property rights. The results indicate that the CFO’s doubling as the Board Secretary can distinctly improve the quality of corporate disclosure in listed companies; the CFO’s holding concurrently the post of the Board Secretary can improve noticeably the disclosure quality of listed companies in regions with a high degree of government intervention; the CFO’s also serving as the Board Secretary can improve the disclosure quality of non-state-owned listed companies. Moreover, this paper presents a reasonable explanation for the phenomenon that increasingly more CFOs are serving as the Board Secretaries simultaneously via empirical study. Lastly, conclusions of this study can provide empirical evidence for the appointment of the Board Secretary in listed companies.